Proceedings of the 7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2019
DOI: 10.7712/120119.7207.19727
|View full text |Cite
|
Sign up to set email alerts
|

3d Detailed Modeling of Reinforced Concrete Frames Considering Accumulated Damage During Static Cyclic and Dynamic Analysis – New Validation Case Studies

Abstract: The study of the hysteretic behavior of reinforced concrete members that undergo static cyclic and dynamic loading conditions in cases where the loading level is close to their carrying capacity, is a challenging open research subject, which currently is being investigated by many researchers. The development of an objective and robust 3D constitutive modeling approach that will be able to account for the accumulated material damage and stiffness deterioration is of great importance in order to realistically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Conclusively, the mesh size misconception is not valid in this case, thus the authors strongly believe that this research work is a proof that the under study material model performs numerically well when combined with the finite element method and in a similar manner with any other constitutive material model currently available in the international literature. With the only difference, that it outperforms them when used with coarser meshes (AlHamaydeh et al, 2017;Engen et al, 2017;Gravett et al, 2019;Markou, 2013Markou, , 2015Markou, , 2018Markou and AlHamaydeh, 2018;Markou and Genco, 2019;Papadrakakis, 2013, 2015;Markou et al, , 2017Markou et al, , 2018aMarkou et al, , 2018bMarkou et al, , 2019aMarkou et al, , 2019bMourlas et al, 2016Mourlas et al, , 2017aMourlas et al, , 2017bMourlas et al, , 2017cMourlas et al, , 2018Mourlas et al, , 2019aMourlas et al, , 2019bMourlas et al, , 2019cSaadi et al, 2018). laboratory technicians of the Civil Engineering Department of the University of Pretoria, during the experimental campaign that was performed during this research work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusively, the mesh size misconception is not valid in this case, thus the authors strongly believe that this research work is a proof that the under study material model performs numerically well when combined with the finite element method and in a similar manner with any other constitutive material model currently available in the international literature. With the only difference, that it outperforms them when used with coarser meshes (AlHamaydeh et al, 2017;Engen et al, 2017;Gravett et al, 2019;Markou, 2013Markou, , 2015Markou, , 2018Markou and AlHamaydeh, 2018;Markou and Genco, 2019;Papadrakakis, 2013, 2015;Markou et al, , 2017Markou et al, , 2018aMarkou et al, , 2018bMarkou et al, , 2019aMarkou et al, , 2019bMourlas et al, 2016Mourlas et al, , 2017aMourlas et al, , 2017bMourlas et al, , 2017cMourlas et al, , 2018Mourlas et al, , 2019aMourlas et al, , 2019bMourlas et al, , 2019cSaadi et al, 2018). laboratory technicians of the Civil Engineering Department of the University of Pretoria, during the experimental campaign that was performed during this research work.…”
Section: Discussionmentioning
confidence: 99%
“…Further development and use of the 3 D detailed modeling approach was presented in AlHamaydeh et al (2017); Gravett et al (2019); Markou (2015Markou ( , 2018; Markou and Genco (2019); Markou and Papadrakakis (2015); Markou et al ( , 2017Markou et al ( , 2018aMarkou et al ( , 2018bMarkou et al ( , 2019aMarkou et al ( , 2019b; Mourlas et al (2016Mourlas et al ( , 2017aMourlas et al ( , 2017bMourlas et al ( , 2017cMourlas et al ( , 2018Mourlas et al ( , 2019aMourlas et al ( , 2019bMourlas et al ( , 2019c; Saadi et al, (2018), where the adoption of relatively large hexahedral elements was assumed. This assumption was solely based on computational restrictions and was not related to the fact that the proposed method was not suitable when finer meshes were used.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted here that, the developed modal algorithm incorporated in ReConAn FEA [35] and its ability to accurately predict the fundamental modes of RC structures was validated through the use of experimental data found in the international literature, whereas the validation was published in [28,29,30,23]. Gravett et al [24] used the developed algorithm in the study of 2-,4-,6-,8-,10-and 20-storeys RC buildings and their dynamic response, while the algorithm was also recently used for the investigation of the SSI phenomenon and its effect on the fundamental period of multi-storey RC structures [6].…”
Section: Numerical Investigation Of Wind Turbine Structures With Sfsi...mentioning
confidence: 99%
“…During a seismic excitation, the interaction between the superstructure (building) and the substructure (soil) can become important as it starts to affect the stress-strain distribution within the superstructure, altering the initial expected results [1][2][3]. In general, it has been found that soil-structure interaction (SSI) can increase the fundamental period and the overall damping of the system, thus it is important to consider it in order to eliminate unsafe designs and unexpected damage development [4][5] during an earthquake excitation.…”
Section: Introductionmentioning
confidence: 99%